2014
DOI: 10.12659/msm.890884
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior in Schizophrenia may be Related to Low Lipid Levels

Abstract: BackgroundLifetime suicide mortality in people with schizophrenia is approximately 4–5%, which is higher than in the general population. In mood disorders, many studies and meta-analyses have shown a link between suicidal behavior and low lipid levels, especially that of cholesterol, and some studies have also suggested such a relationship in schizophrenia. Therefore, the aim of the present study was to investigate a possible correlation between suicidal behavior and lipid levels in schizophrenia patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“… No. First author (publication year) References Country Survey time Study design Sampling method Sample size Demographic information Schizophrenia-related information SI-related information Quality assessment score Source of patients Mean age (years) Male gender proportion (%) Average education level (years) Diagnostic criteria a Average onset age (years) Average duration of illness (years) Measure instrument Timeframe of SI 1 Acosta (2020) [ 73 ] Spain 2012−2015 Cohort Non-probability sampling 133 Outpatient 46.7 69.2 Categorical data ICD-10 NR 20.84 Scale Lifetime 4 2 Ainiyet (2014) [ 37 ] Poland Sept. 2005−Jun. 2006 Cross-sectional Non-probability sampling 148 Inpatient 32 46.63 NR DSM-IV NR 7 Interview 3-month 4 3 Dell’Osso (2012) b [ 25 ] Italy NR Cross-sectional Non-probability sampling 79 Mixed 36.28 69.6 Categorical data DSM-IV NR NR Question Lifetime 5 4 Duko (2018) [ 74 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… No. First author (publication year) References Country Survey time Study design Sampling method Sample size Demographic information Schizophrenia-related information SI-related information Quality assessment score Source of patients Mean age (years) Male gender proportion (%) Average education level (years) Diagnostic criteria a Average onset age (years) Average duration of illness (years) Measure instrument Timeframe of SI 1 Acosta (2020) [ 73 ] Spain 2012−2015 Cohort Non-probability sampling 133 Outpatient 46.7 69.2 Categorical data ICD-10 NR 20.84 Scale Lifetime 4 2 Ainiyet (2014) [ 37 ] Poland Sept. 2005−Jun. 2006 Cross-sectional Non-probability sampling 148 Inpatient 32 46.63 NR DSM-IV NR 7 Interview 3-month 4 3 Dell’Osso (2012) b [ 25 ] Italy NR Cross-sectional Non-probability sampling 79 Mixed 36.28 69.6 Categorical data DSM-IV NR NR Question Lifetime 5 4 Duko (2018) [ 74 ] …”
Section: Resultsmentioning
confidence: 99%
“…2a ), and the pooled point prevalence of SI was 29.9% (95% CI: 24.2−35.6%; I 2 = 89.5%). The 3-month prevalence [ 37 ], 1-year prevalence [ 20 ], and prevalence of SI during more than 1 month period before admission [ 38 ] was 44.6%, 16.2%, and 19.6%, respectively. The lifetime prevalence of SP was 44.3% [ 25 ], and point prevalence of SP in two studies was 6.4% [ 26 ] and 13% [ 24 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, Janusz et al [23] have reported that total cholesterol, LDL cholesterol, total lipids, and triglycerides are significantly lower in patients with schizophrenia who had a suicidal attempt. In terms of gender differences, we must emphasize that females may be especially sensitive to dieting-induced changes in the central serotonin function [39].…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have focused on the search of biological markers that may be linked to suicidal behavior and can be used as an additional instrument for prevention and therapeutic action. It has been found that metabolic deregulation, especially altered lipid profile including low total cholesterol (TC) and low-density lipoproteins-cholesterol (LDL-c) levels, may underlie higher suicide risk in patients with schizophrenia [1, 3]. A number of studies have investigated a possible link between low serum cholesterol and psychiatric symptoms, especially suicidal behavior [36].…”
Section: Introductionmentioning
confidence: 99%
“…There is even information that aggressive behaviour increased with the reduction in cholesterol levels in the field of anti-hyperlipidemic therapy. 18 Studies have demonstrated that low serum cholesterol was related to suicidal behaviour in antisocial personality disorder 19 and schizophrenia 20 patients. It was found that the decrease in cholesterol levels reduced serotonin receptor sensitivity by altering the fluidity of neuron membranes.…”
Section: Discussionmentioning
confidence: 99%